Establishment of Nrf2-deficient HaCaT and immortalized primary human foreskin keratinocytes and characterization of their responses to ROS-induced cytotoxicity. (December 2019) - Choi, Moonju; Park, Minkyung; Lee, Sungjin; Lee, Jeong Woo; Choi, Won Jun; Lee, Choongho
Abstract: Nuclear factor erythroid 2-like 2 (Nrf2) is a key transcription factor responsible for the induction of cytoprotective genes when a cell is exposed to reactive oxygen species (ROS). Insufficient ROS neutralization has been associated with undesirable changes in the skin caused by age and disease. In order to mimic the pathological conditions of these oxidative stress-induced skin disorders, we established Nrf2-deficient HaCaT and immortalized human foreskin keratinocyte (iHFK) cell lines via lentiviral transduction of Nrf2-targeting short-hairpin RNAs. Their transcriptional, as well as translational blockage of Nrf2 expression, was verified by using a proteasomal inhibitor (MG132) and well-known Nrf2 activator (α-lipoic acid (ALA)). Reduced expression of NADPH dehydrogenase quinone 1 (NQO-1) and heme oxygenase 1 (HO-1) genes, which are well-characterized downstream targets of Nrf2-mediated transactivation, was also confirmed by using ALA and another Nrf2 activator, marliolide. In general, iHFK cells displayed more enhanced cytotoxicity to menadione, a ROS-generating reference compound, than HaCaT cells. In addition, the Nrf2 deficiency highly potentiated the cytotoxic effects of menadione in both HaCaT and iHFK cells. Interestingly, pretreatment of either ALA or marliolide conferred protection against the ROS induction and the subsequent development of cytotoxicity by menadione in both HaCaT and iHFK cells regardless of the Nrf2 status. These data suggest a possibility for activation of Nrf2-independent ROS detoxification pathways by either ALA or marliolide. These newly established Nrf2-deficient HaCaT and iHFK cell lines should be useful as a highly ROS-sensitive damaged skin model for the study of age-dependent cellular changes in an in vitro setting. Highlights: Nrf2-deficient HaCaT and immortalized human foreskin keratinocyte (iHFK) cells were established. Their Nrf2 deficiency was verified by using a proteasomal inhibitor and Nrf2 activators. They displayed a more pronounced cytotoxicity induced by menadione than control cells. Despite Nrf2 deficiency, two Nrf2 activators conferred them protection against menadione-induced cytotoxicity.